APLIKASI BIOCHAR DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN TANAMAN BAYAM MERAH (Amaranthus tricolor L) - Yonni Oktavio Balompapung; Verry Ch. Warouw; Lientje Th. Karamoy (COCOS, 2021)
SUMMARYYonni Oktavio Balompapung, 14031108021 (2021) Application of Biochar and CowManure on Growth of Red Spinach Plants (Amaranthus Tricolor L). Under theguidance of Dr. Ir. Verry Ch. Warouw, MS as Chairman and Dr. Ir. Lientje Th.Karamoy, MSi as Member.This study aims to examine and find out how much influence the application ofbiochar and cow manure on the growth of red spinach (Amaranthus Tricolor L)plants. This research was conducted in Kakaskasen Village, North Tomohon District,Tomohon City. For pot experiments, soil analysis and cow manure were carried out atthe Laboratory of Chemistry and Soil Fertility, Department of Soil, Faculty ofAgriculture, Sam Ratulangi University, Manado. This research was conducted using acompletely randomized design method consisting of 7 treatments with 5 replicationsin order to obtain 35 experimental pots, where soil control (KT), soil biochar control(KTB) and A, B, C, D, E as mixed growing media biochar and cow manure accordingto the dosage.The results of this study indicate that the application of biochar and cow manureaffects the growth and production of red spinach (Amaranthus Tricolor L.) in thiscase plant height, plant fresh weight and plant dry weight. The higher the dose ofmanure given, the higher the results obtained for plant height, plant fresh weight andplant dry weight.Keywords: Biochar,Cow manure, Red spinach.